SISINGAAN SENI KEMASAN WISATA DI KABUPATEN SUBANG - Tubagus ` Mulyadi (Greget, 2000)
Artistry (of) Sisingaan represent Earing people resistance representasisymbolfirst to colonial pra ctice a period of/to power(of) Dutch. Symbol Power grinding this implied in the form of appearance (of) lion idol which (is) stretcher. While resistance form depicted in moppet figure riding lion, please implies that grind will fail by the rising generation. Artistic (of) this tidiness (of) lebeih focussed [by) (at) show estetik facet, without eliminating meaning which consist in in itKeyword: Sisingaan, artistic (of] tidiness